Reproductive flexibility in South American camelids: First records of alternative mating tactics in wild guanacos (Lama guanicoe) - Panebianco, Antonella (2020)
Intraspecific variation in mating behavior has been documented in diverse taxa, including ungulates. Here, we report and describe for the first time the existence of alternative mating tactics in a wild guanaco (Lama guanicoe) partially migratory population. We document (1) a resource-defense tactic, widely reported for different populations; and (2) a clustered territorial tactic, adopted by the solo territorial males of this population. Our results highlight the reproductive flexibility of this species and its relationship with external factors that could be influencing it.